2009
DOI: 10.1007/s11547-009-0476-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose unenhanced CT protocols according to individual body size for evaluating suspected renal colic: cumulative radiation exposures

Abstract: Although radiation dose is nearly double in overweight-obese patients undergoing MDCT, it remains lower than that delivered by a standard-dose protocol. Patients with flank pain, who are often young, are at increased risk for serial CT examinations. Use of a low-dose protocol is mandatory in both normal-weight and obese patients to minimise radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Thomas calculate effective dose in abdomen-pelvic examination for adults, by calculating DLP and using the related conversion factor to estimate the effective dose, 5.9mSv was achieved [31]. This study reported a linear relationship between increasing BMI and DLP with proper compliance and effective dose described, which is fully consistent with the results of Tartari [32].…”
Section: Discussionsupporting
confidence: 85%
“…Thomas calculate effective dose in abdomen-pelvic examination for adults, by calculating DLP and using the related conversion factor to estimate the effective dose, 5.9mSv was achieved [31]. This study reported a linear relationship between increasing BMI and DLP with proper compliance and effective dose described, which is fully consistent with the results of Tartari [32].…”
Section: Discussionsupporting
confidence: 85%
“…This may be accomplished by not doing a CT or by performeing a “low‐dose” CT scan. While data about low‐dose CT protocols for renal colic have been published in Europe, and the use of low‐dose protocols has been suggested in the United States, to our knowledge no large trial of kidney stones diagnosed in the ED in the United States using low‐dose protocols in actual patients has been published . Data from our institution examining CTs for renal colic between 1996 and 2002 found an effective radiation dose of approximately 6.5 mSv for single‐detector CTs and 8.5 mSv for multidetector CT .…”
Section: Discussionmentioning
confidence: 92%
“…Utilization of point‐of‐care ultrasound (POCUS) can be used in acute settings to rapidly rule in the diagnosis of renal colic and to avoid nonselective, standard‐dose CT scan examination for all renal colic patients . It has been suggested that ultrasound‐first approach can avoid radiation exposure in about 70% of cases .…”
mentioning
confidence: 99%